Study on some Aspects of Irrawady River Dolphin Orcaella brevirostris Gray in Chilika Lake, Orissa - Sahu, H. K.; Kar, S. K.; Patnaik, S. K. (Indian Forester, 1998)
Chilika wetland ecosystem in Orissa provides an ideal habitat to a small population ofIrrawady river Dolphins Orcaella brevirostris. Its occurrence was first recorded in Chilika by Annandale during 1915 and subsequent studies confirmed their existence in this brackish water lake. The present study deals with status, movement, feeding, morphometry and behavioural aspects of this threatened cetacean and recommends preservation of this isolated population along with their habitats.